THE INFLUENCE OF SOCIAL MEDIA MARKETING AND BRAND IMAGE ON PURCHASE DECISIONS AT SHOPEE THROUGH PURCHASE INTEREST AS A MEDIATION VARIABLE - Bilgah Bilgah; Nurzalinar Joesah (Jurnal Ekonomi, 2022)
This study aims to determine the effect of Social Media Marketing and Brand Image on Purchase Decisions with Purchase Intention as an intervening variable at Shopee. This study uses primary data by taking data from questionnaires. The sampling technique in this study is probability sampling so that the number of samples used is 100 people. The data analysis technique in this study used (SEM) structural equation modeling with the help of smartPLS to be able to solve the problems and hypotheses that have been formulated in this study and used to test the relationships between variables. The results of this study indicate that Social Media Marketing has no effect on Purchase Decision, Brand Image has a positive and significant effect on Purchase Decision, Social Media Marketing has a significant effect on Purchase Intention, Brand Image has a significant effect on Purchase Intention, Purchase Intention has a significant effect on Purchase Decision Purchasing, Social Media Marketing has a significant effect on Purchase Decision through Purchase Interest and Brand Image influences Purchase Decision through Purchase Interest. Purchase intention is able to have a positive and significant direct influence on the relationship between Social Media Marketing and Brand Image on purchasing decisions